Silver linings a Rose Harbor novel - Macomber, Debbie (New York Ballantine Books, 2015)
"Set in Cedar Cove's charming Rose Harbor Inn, Debbie Macomber's...novel follows innkeeper Jo Marie and two new guests as they seek healing and comfort, revealing that every cloud has a silver lining, even when it seems difficult to find"--
102805
Keywords: Hotelkeepers; Interpersonal relations; Man-woman relationships; Fiction / Romance / Contemporary; Fiction / Contemporary Women; Fiction / Sagas; Love stories